Сarbon-containing shields for protection of human body against electromagnetic radiation - M. S. Al-Mahdawi; E. S. Belousova (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of the study of electromagnetic radiation shields based on fibrous material containing carbon black particles are presented. They are designed to protect the human body from the negative effect of electromagnetic waves.